Financial well-being among public employees in Malaysia: a preliminary study - Mokhtar, Nuradibah; Abdul Rahim @ Abdul Wahab, Husniyah; Sabri, Mohamad Fazli; Abu Talib, Mansor (Canadian Center of Science and Education, 2015)
Public employee’s innovativeness, responsiveness, efficiency and friendliness in services are the core prescriptions to enhance the competitiveness of one’s country. Financial well-being and employees are two aspects that consequently related with each other that have received substantial deliberation from researchers, employers and financial advisor. Financial well-being can affect both direct and indirectly towards an individual, team and also organization. Changes in employee’s financial well-being level whether it becomes high or low will affect their job performance. The purpose of this study is to discuss the level of public employee’s financial well-being in Malaysia as well as to examine the determinants of financial well-being. A total of 73 questionnaires have been distributed through e-survey (email based) using convenient sampling technique in order to conduct this pilot test (pre-test). Only 30 public employees have participated in this study. The results identified that majority of public employees is at the moderate level of financial well-being. Even so, appropriate action should be taken through financial education in order to prevent worst case scenario in the future.